2021
DOI: 10.3233/bmr-200100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body composition on Functional Movement Screen scores in elite youth male soccer players

Abstract: BACKGROUND: The Functional Movement Screen (FMS) is a clinical assessment tool used to determine musculoskeletal dysfunctions and asymmetries in athletes. OBJECTIVE: The aim of this study was to investigate whether FMS scores differed between elite youth male soccer players with low body fat percentage and those with normal body fat percentage and between those with and without a history of soccer injury. METHODS: Fifty-three elite youth male soccer players were included in the study. The participants’ injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A recent study found no significant differences ( p > 0.05) in the total FMS score, movement score, mobility score, or stabilization score between young male soccer players who either lean (less than 6% body fat) or normal (6–18% body fat) [ 97 ]. After following a corrective exercise program involving the use of medicine balls, elastic bands, foam rollers, self- and partner stretching, and strength and stability exercise, there was an increase in the total FMS score as well as the movement, mobility, and stabilization sub scores in the training group but not the control group [ 46 ].…”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study found no significant differences ( p > 0.05) in the total FMS score, movement score, mobility score, or stabilization score between young male soccer players who either lean (less than 6% body fat) or normal (6–18% body fat) [ 97 ]. After following a corrective exercise program involving the use of medicine balls, elastic bands, foam rollers, self- and partner stretching, and strength and stability exercise, there was an increase in the total FMS score as well as the movement, mobility, and stabilization sub scores in the training group but not the control group [ 46 ].…”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
“…Many of the studies have been descriptive in nature, evaluating movement competencies of young athletes in soccer [ 46 , 47 , 50 , 51 , 53 , 56 , 66 , 69 , 86 , 97 , 99 , 100 ], Australian football [ 101 ], football [ 99 , 102 ], basketball [ 70 ], baseball [ 80 ], floorball [ 64 ], swimming [ 54 , 103 ], ice hockey [ 42 , 43 , 63 ], karate [ 62 ], judo [ 88 ], tennis [ 73 , 74 ], cross country and volleyball [ 61 , 99 ], cricket [ 94 ], handball [ 79 ], lacrosse [ 55 , 102 ], Wushu (Taiji, Changquan, Nanquan) [ 77 ], and surfing [ 86 ].…”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 3 more Smart Citations